Modelling the optimal delivery of spare parts to vessels: Comparison of three different scenarios. Issue 1 (1st January 2021) - Vukić, Luka; Stazić, Ladislav; Pijaca, Marija; Peronja, Ivan
Abstract: Spare parts management on ships is a notable segment of total transportation costs being able to become a significant factor in the process of cost optimization, given the increasingly unpredictable economic circumstances and unstable geopolitical relations. This study aims to determine the optimal parcel delivery scenario to the ship based on the created mathematical model, using the delivery option of air freight service, express service, and consolidation service on the examined transportation route. The model uses a predefined set of variables such as total shipping cost, delivery time, and total distance, which were compared according to the different conditions of parcel delivery requirements and additional weight units. The research results show that the air freight delivery scenario is the optimal solution when the total cost is considered the most weighted function value. When time is set the most significant, the express delivery scenario proves to be the optimal solution. In the case when the distance is considered the most weighted function value, both first and second scenarios are optimal. According to the model results, the consolidation service was neither economically preferred nor advantageous comparing to the alternative delivery options. However, in certain circumstances, full exploitation of its economic advantages is possible. These research findings significantly contribute to the efficiency and productivity of the logistic chain. They enable decision-makers to empirically determine the optimal network of parcel delivery between two locations.